Early Judaeo-Christianity - Mimouni, Simon Claude, 1949- (Leuven)
xiv, 461 s.
Keywords: "The essays presented here are the results of over ten years study. To appreciate the development of Christianity in the ancient world, knowledge of the Jewish parameter remains as important as that of the pagan parameter. The question is to know when, how and why Christianity left Judaism to become an independent religion. In other words, at what moment did the disciples of Jesus consider themselves as no longer Jews or pagans, but rather as Christians? What are the historian's sources? Christianity built its history through the diligence of its theologians. The historian must therefore detach himself from this perspective, explaining the traditional sources, recovering in them historical elements which facilitate bringing to light the gradual separation." --